PENGARUH MODEL SELF-DIRECTED LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMA NEGERI 1 INDRALAYA UTARA - Ratih; Sri Artati Waluyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Self-Directed Learning (SDL) model on students’ learning motivation at SMA Negeri 1 Indralaya Utara. SDL is considered an approach that allows students to set goals, manage strategies, and reflect on their learning process, thereby strengthening intrinsic motivation. The study employed a quasi-experimental method with a non-equivalent control group design, involving one experimental and one control class. Data were collected through observation questionnaires on learning motivation during the learning process. Instrument testing confirmed validity and reliability with a Cronbach’s Alpha of 0.873. The data were normally distributed and homogeneous. The t-test showed a value of 3.421 with a p-value of 0.001 (< 0.05), indicating a significant difference between the experimental and control groups. The experimental group achieved a higher mean score (82.15) compared to the control group (74.32). These findings support Knowles’ SDL concept and Deci and Ryan’s Self-Determination Theory, which highlight autonomy and competence as key factors for intrinsic motivation. The study concludes that SDL is effective at the secondary school level, and teachers are encouraged to act as facilitators who foster students’ learning independence.